Spray granulation of Fe and C nanoparticles and their impedance match for microwave absorption. Issue 3 (March 2018) - Huang, H.; Gao, Y.; Fang, C.F.; Wu, A.M.; Dong, X.L.; Kim, B.S.; Byun, J.H.; Zhang, G.F.; Zhou, D.Y.
Abstract: The microwave absorbents of Fe and C nanoparticles as magnetic loss and dielectric loss material respectively were composited with the polyvinyl alcohol (PVA) as binder by spray granulation method. The electromagnetic parameters of Fe and C composite particles were analyzed by vector network. The complex permittivity and magnetic permeability of Fe and C composite particles matched well with increasing C nanoparticle content, and then the microwave loss property was improved. A minimum reflection loss (RL) of −42.7 dB at 3.68 GHz for a composite with 4.6 mm in thickness can be obtained when the content ratio of the C nanoparticles, the modified Fe nanoparticles and the PVA is 21:49:30 (Sample 3).